Dementia care model: promoting personhood through co-production - Bosco, Alessandro; Schneider, Justine M.; Coleston-Shields, Donna Maria; Orrell, Martin (Elsevier, 2019)
Background Despite robust evidence on its effectiveness, current approaches that aspire to person-centred care (PCC) frequently locate people with dementia as passive recipients rather than as active agents in the care process. We define active involvement in care as ‘co- production’. In order to investigate co-production, we set out to review the evidence concerning personhood and dignity in dementia care.